Teknik Pembelian Terselubung Dalam Penyidikan Tindak Pidana Narkotika - Sapto Winengku; Umar Ma’ruf (Jurnal Hukum Khaira Ummah, 2020)
One of the techniques used by investigators in conducting an investigation of narcotic crime is a covert purchasing technique. The investigator himself and / or use other people to purchase narcotics with supervised then arrested the perpetrator along with the evidence. The authority of Polri investigators to make a covert purchase under Article 75 hurif j and Article 79 of Law Number 35 Year 2009 concerning Narcotics is to conduct investigation techniques of veiled purchases and submission under supervision.Narcotics crime is a violation of the criminal provisions in Law Number 35 Year 2009 on Narcotics, either directly related to the misuse of narcotics or acts related to the misuse of narcotics. The covert purchase technique in the investigation of narcotic crime is the undercover buy technique which is done to search and collect the evidence which with the evidence makes light of the narcotic crime and to find the suspect.Covert purchase techniques in narcotic drug criminal investigations are vulnerable to misuse. Investigators may trap someone by ordering a covert purchase and / or supervised submission then making the arrest. Therefore, there is a need to restrict the purchase and / or covert delivery in the investigation of narcotic crime. For example a covert purchase can only be done by the investigator himself and prohibit the acceptance of community members.Keywords: Covert purchase, Investigation